Konsistensi Al-Qur’an Sebagai Mukjizat - Mirwan Sudarmawan Rifai; Muhammad Irham; Andi Miswar (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the internal consistency of the Qur’an as an essential aspect of its miraculous nature (i‘j?z al-Qur’?n). As a revealed text delivered gradually over more than two decades, the Qur’an presents a unique phenomenon characterized by coherence and the absence of internal contradictions. This research employs a qualitative approach using library research methods, along with thematic (maudh?‘?) analysis of relevant Qur’anic verses. The findings indicate that the consistency of the Qur’an can be observed in several key dimensions, including linguistic, thematic, normative, and narrative aspects. Furthermore, this study finds that claims of inconsistency raised in certain orientalist studies often stem from partial readings and methodological limitations that overlook the distinctive nature of the Qur’an as a revealed text. Therefore, the internal consistency of the Qur’an not only reinforces the theological argument of its divine origin but also represents an epistemological phenomenon reflecting the coherence and unity of its meaning system.